Answer: a. It is commonly referred to as the arithmetic average.
b. It is algebraically defined (that is, there is an equation you can use to calculate its value).
c. It is easily influenced by extreme scores.
Step-by-step explanation:
The mean is also referred to as the "average" and it is gotten by adding every number and the dividing the value gotten by the number of the numbers used for the calculation.
It should be noted that the mean is algebraically defined and can be easily influenced by extreme scores.
Answer:
The equation 2d + 18 = 24 can help find the number of days Jerry has been doing sit-ups.
Step-by-step explanation:
During the first day, Jerry did 18 sit-ups, and he proceeded to do 2 more sit-ups each following day, so the expression to represent this situation is 2d + 18. Because he did 24 sit-ups today, to find the number of days he did sit-ups, the equation to solve is 2d + 18 = 24.
Answer:
-139
Step-by-step explanation:
Evaluate 1/4 (4 x^3 - 2 y - 2 z^3) y^2 - 16 x^2 where x = 2, y = -5 and z = 3:
(4 x^3 - 2 y - 2 z^3)/4 y^2 - 16 x^2 = (4×2^3 - -5×2 - 2×3^3)/4×(-5)^2 - 16×2^2
(4×2^3 - 2 (-5) - 2×3^3)/4×(-5)^2 = ((4×2^3 - 2 (-5) - 2×3^3) (-5)^2)/4:
((4×2^3 - 2 (-5) - 2×3^3) (-5)^2)/4 - 16×2^2
(-5)^2 = 25:
((4×2^3 - 2 (-5) - 2×3^3) 25)/4 - 16×2^2
2^3 = 2×2^2:
((4×2×2^2 - 2 (-5) - 2×3^3) 25)/4 - 16×2^2
2^2 = 4:
((4×2×4 - 2 (-5) - 2×3^3) 25)/4 - 16×2^2
2×4 = 8:
((4×8 - 2 (-5) - 2×3^3) 25)/4 - 16×2^2
3^3 = 3×3^2:
((4×8 - 2 (-5) - 23×3^2) 25)/4 - 16×2^2
3^2 = 9:
((4×8 - 2 (-5) - 2×3×9) 25)/4 - 16×2^2
3×9 = 27:
((4×8 - 2 (-5) - 227) 25)/4 - 16×2^2
4×8 = 32:
((32 - 2 (-5) - 2×27) 25)/4 - 16×2^2
-2 (-5) = 10:
((32 + 10 - 2×27) 25)/4 - 16×2^2
-2×27 = -54:
((32 + 10 + -54) 25)/4 - 16×2^2
| 3 | 2
+ | 1 | 0
| 4 | 2:
(42 - 54 25)/4 - 16×2^2
42 - 54 = -(54 - 42):
(-(54 - 42) 25)/4 - 16×2^2
| 5 | 4
- | 4 | 2
| 1 | 2:
(-12×25)/4 - 16×2^2
(-12)/4 = (4 (-3))/4 = -3:
-3×25 - 16×2^2
2^2 = 4:
-3×25 - 164
-3×25 = -75:
-75 - 16×4
-16×4 = -64:
-64 - 75
-75 - 64 = -(75 + 64):
-(75 + 64)
| 7 | 5
+ | 6 | 4
1 | 3 | 9:
Answer: -139
<h2>
Answer: y + 7 = -3 (x - 1)</h2>
Step-by-step explanation:
The slope of the line (m) = (y₂ - y₁) ÷ (x₂ - x₁)
= (- 7 - 8) ÷ ( 1 - (- 4))
= - 15 ÷ 5
= - 3
We can now use the point-slope form to write the equation for this line:
y - y₁ = m(x - x₁) where (x₁ , y₁) = (1, -7)
y - (-7) = -3 ( x - 1)
y + 7 = -3 (x - 1)